Pemberdayaan Masyarakat Dalam Dukungan Suami Dengan Pemilihan Jenis Kontrasepsi Iud Pada Wanita Usia Subur di Kelurahan Ladang Bambu Kecamatan Medan Tuntungan - Suriati Lubis; Desi Anggraini (Indonesian Journal Publisher, 2021)
Intra-Uterine Devices are an effective, safe and convenient contraceptive option for many women Husband support in family planning is a tangible form of men's concern and responsibility. Husbands who are the head of the family must be wise in making decisions, both for themselves and for their family members including their wives. This community service aims to increase husband support with the selection of Intra uterine Device contraception in women of childbearing age. subjects in the community service activities were women of childbearing age in Mango Village, Ladang Bambu District, totaling 15 people. At the initial stage, an approach was made to the residents to deliver counseling material using the lecture method, the implementation of immunization assisted by the village midwife and continued with a question and answer session.Community service activities with the title